Teacher’s Perception of Self-Assessment in English Writing Competency for Junior High School Students - Adiguna, I Wayan Bayu; Dewi, Ni Luh Putu Eka Sulistia; Paramartha, Anak Agung Gede Yudha; Wahyuni, Luh Gede Eka (Jurnal Pendidikan Bahasa Inggris undiksha, 2023)
Self-assessment provides many benefits in learning English, especially in terms of writing ability. This study aims to analyze teachers' perceptions and challenges that teachers find of the application of selfassessment in students' writing competencies at everal junior high school in Nusa Penida. This study used mixed method explanatory design as the research approach. The subjects of this study were EFL secondary teachers in three junior high school. Quantitative data in this study used a questionnaire to obtain accurate data related to teacher perceptions. Qualitative data used semistructured interviews. The interview statement was adjusted to the theory in the questionnaire. The data collection from questionnaire is analyzed by using Excel to find out the median of the questionnaire. In the interview, the data analyzed using thematic analysis. The result of this study shows that teachers have perceptions that tend to be positive towards the implementation of self-assessment in writing competency as a means for students to self-reflect, help students get feedback, develop writing ideas to be better confidently and independently. Teachers also experience obstacles in implementing self-assessment that the purpose of selfassessment is still not well understood by students.